2006
DOI: 10.1074/jbc.m604680200
|View full text |Cite
|
Sign up to set email alerts
|

Crn7 Interacts with AP-1 and Is Required for the Maintenance of Golgi Morphology and Protein Export from the Golgi

Abstract: Crn7 is a novel cytosolic mammalian WD-repeat protein of unknown function that associates with Golgi membranes. Here, we demonstrate that Crn7 knockdown by small interfering RNA results in dramatic changes in the Golgi morphology and function. First, the Golgi ribbon is disorganized in Crn7 KD cells. Second, the Golgi export of several marker proteins including VSV envelope G glycoprotein is greatly reduced but not the retrograde protein import into the Golgi complex. We further establish that Crn7 co-precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
1
31
1
Order By: Relevance
“…Disruption of AP-1B function by microinjection of AP-1B antibody (Cancino et al, 2007) or knockdown of AP-1B has been reported to block the sorting of VSVG to the basolateral surface in polarized epithelial cells. In nonpolarized cells, the interaction of AP-1 and Crn7 was shown to be required for the export of VSVG from the Golgi (Rybakin et al, 2006). The cell types used in this current study are nonpolarized and, therefore, most likely express exclusively AP-1A.…”
Section: A Novel Function For Eps15 In the Transport Of Nascentmentioning
confidence: 87%
“…Disruption of AP-1B function by microinjection of AP-1B antibody (Cancino et al, 2007) or knockdown of AP-1B has been reported to block the sorting of VSVG to the basolateral surface in polarized epithelial cells. In nonpolarized cells, the interaction of AP-1 and Crn7 was shown to be required for the export of VSVG from the Golgi (Rybakin et al, 2006). The cell types used in this current study are nonpolarized and, therefore, most likely express exclusively AP-1A.…”
Section: A Novel Function For Eps15 In the Transport Of Nascentmentioning
confidence: 87%
“…It is possible that the N-terminal half of CRN7 has a negative effect on Tob degradation and that a conformational change in CRN7 in response to cellular signaling modulates the activity. CRN7 is known to participate in the regulation of Golgi trafficking [18,19]; however, its involvement in proteosome-mediated degradation has not been reported. We show here for the first time that CRN7 forms a novel E3 ligase complex.…”
Section: Discussionmentioning
confidence: 99%
“…RNA interference-mediated inhibition of CRN7 results in morphological changes in the Golgi apparatus and the subsequent disruption of anterograde Golgi-to-plasma membrane transport [19]. Since CRN7 interacts with the clathrin adaptor AP-1, the function of CRN7 may be important for clathrin-dependent membrane trafficking [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The following siRNA were used: targeting human m1-adaptin -validated siRNA cat. # SI00299187 (Qiagen; no sequence information provided by vendor); targeting human Crn7 -siRNA (8) 2454 [7]; control: siCONTROL Non-Targeting siRNA Pool cat. # D-001206-13 (Dharmacon; no sequence information provided by vendor).…”
Section: Methodsmentioning
confidence: 99%
“…Such proteins have been studied in Caenorhabditis elegans and Drosophila melanogaster, and mutant phenotypes suggest that they play a role in vesicular trafficking, embryonic axis formation and axonal guidance [4,5]. We recently demonstrated that the only human dual WD domain coronin, the Coronin-7 (Crn7), differs from the rest of the family in that it localizes to the Golgi complex and is required for the maintenance of Golgi morphology and for protein export from the Golgi [6,7]. Depletion of Crn7 by RNAi leads to Golgi breakdown and retention of VSVG in the Golgi upon a shift to the permissive temperature.…”
Section: Introductionmentioning
confidence: 99%